Mortality of iron miners in Lorraine (France): relations between lung function and respiratory symptoms and subsequent mortality. Issue 11 (November 1993) - Chau, N; Benamghar, L; Pham, Q T; Teculescu, D; Rebstock, E; Mur, J M
Abstract : An increased mortality from lung and stomach cancer was found in previous studies on Lorraine iron miners. A detailed analysis, however, was not possible due to the lack of data for survivors. In this study the cohort included 1178 workers selected at random from all the 5300 working miners aged between 35 and 55 at the start of the follow up period, which ranged from 1975 to 1985. Occupational exposures and tobacco consumption, lung function tests, and respiratory symptoms were assessed for each subject in 1975, 1980, and 1985. This study confirmed the excess of lung cancer (standardised mortality ratio (SMR) = 389, p < 0.001) and of stomach cancer (SMR = 273, p < 0.05). There was no excess of lung cancer in non-smokers and moderate smokers (< 20 pack-years) or the miners who worked only at the surface or underground for less than 20 years. A significant excess (SMR = 349, p < 0.001) was found in moderate smokers when they worked underground for between 20 and 29 years. Heavy smokers (over 30 pack-years) or subjects who worked underground for more than 30 years experienced a high risk: SMR = 478 (p < 0.001) for moderate smokers who worked underground for over 30 years; 588 (p < 0.001) for heavy smokers who worked underground for between 20 and 29 years; and 877 (p < 0.001) for heavy smokers who worked underground for over 30 years. This showed an interaction between smoking and occupational exposure. The excess mortality from lung cancer was because there were some subjects who died young (from 45 years old). Comparison with the results of a previous study showed that additional hazards produced by diesel engines and explosives increased the mortality from lung cancer. The SMR was higher than 400 (p < 0.001) from 45 years old instead of from 56 years. A relation was found between a decrease in vital capacity (VC), forced expiratory volume in one second (FEV1) and of FEV1/VC and mortality from all causes and from lung cancer in heavy smokers or men who had worked underground for more than 20 years. Respiratory symptoms were related to mortality from lung cancer among smokers (moderate and heavy) who worked underground for more than 20 years. It is considered that the risk of lung cancer in the Lorraine iron miners was mainly due to dust, diesel engines, and explosives although the role of low exposure to radon daughters could not be totally excluded.